Suppression of nonstationary sinusoidal interference using transform domain median filtering - Kasparis, Takis (My University, 1993)
A novel technique for the suppression of sinusoidal interference by using transform domain median filtering is proposed. The most important advantage of this new technique is that estimation of the interference frequency is not needed. Other important advantages are also discussed. Residual errors are examined and compared with that of notch filtering. Experimental results with random binary sequences are presented.
Keywords: Electric filters; Image processing; Binary system (Mathematics)